MUSLIM FAMILY COMMUNICATION IN DEALING WITH FATHERLESSNESS AND ITS IMPACT ON CHILD GROWTH IN MEDAN JOHOR CITY - Lumban Gaol, Desi Ratna Sari; Sazali, Hasan (International Journal of Cultural and Social Science, 2026)
This study aims to analyze Muslim family communication in dealing with fatherlessness and its implications for children's psychosocial development and communication behavior in Medan Johor City. The study uses a qualitative approach with a phenomenological method to understand the subjective experiences of mothers, children, and father substitute figures in everyday life. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña through the stages of data condensation, data presentation, and conclusion drawing. The results show that fatherlessness not only represents the physical absence of a father, but also the weakening of the father's communicative and affective function in the family. In this context, the mother becomes the main center of interaction, emotional management, and transmission of family meaning, while children form diverse interpretations of the father figure according to the cause of fatherlessness, such as death, divorce, migration, or work commitments. The novelty of this study lies in its placement of fatherlessness as a communicative reality in Muslim families, not merely as a psychological or social problem, but as a process of negotiation of meaning, role substitution, and the formation of children's identities through symbolic interaction. Theoretically, this study expands the study of family communication by demonstrating that father absence alters the architecture of domestic communication, attachment patterns, and children's emotional validation. Its scientific implications emphasize the importance of a family communication approach sensitive to Islamic values ??to understand Muslim families' adaptation strategies in maintaining relationship stability and child development in the face of fatherlessness.